Aestheticism in the theory of custom - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2021)
The nature of learning processes as well as evolutionary considerations suggest that aesthetic judgement is of central importance in the formation of custom. Learning and extrapolation rely on evaluations of non-instrumental features like simplicity, analogy, straightforwardness, and clarity. Further, learning is particularly effective if it is driven by an active desire to uncover new regularities, rather than merely gathering information in a passive way.From an evolutionary perspective, learning has evolved as an adaptation to fast and transitory environmental changes which cannot be effectively traced by the slow and long-term evolutionary processes which take place on the genetic level. The evolutionary raison d'être of learning is to enable the individual to incessantly search for upcoming new regularities, and to act appropriately on them. As learning depends on aesthetic judgement, the evolutionary selection for learning implies an evolutionary molding of an aesthetic sense, and a preference for patterns and patterned action which ultimately leads to the formation of custom and social learning. The paper presents, thus, an evolutionary underpinning for the behavioral tendencies underlying my theory of custom.
urn:nbn:de:bvb:19-epub-76603-5
Keywords: B15; B25; B52; D02; D23; E14; 330; Institutional economics; evolution; evodevo; evo-devo; aesthetics; variation; selection; institutional economics; social psychology; rule-learning